Gender differences in factors associated with the health literacy of hospitalized older patients with chronic diseases: A cross-sectional study - Sun, Shuting; Lu, Jinjin; Wang, Yawen; Wang, Ya; Wu, Lihao; Zhu, Saiqiong; Zheng, Xiuyun; Lu, Xueqin; Xu, Hongbo (Frontiers in Public Health, 2022)
Background: To identify gender differences in factors associated with the health literacy of hospitalized older patients with chronic diseases. Methods: A total of 471 hospitalized older patients with chronic diseases in four hospitals were investigated from May 2019 to June 2020. The self-developed demographic information questionnaire, the “Health Literacy Scale for Patients with Chronic Diseases” and the “Self-Efficacy for Managing Chronic Diseases 6-item Scale” were applied in this study. Multiple linear regression was used to assess the factors influencing health literacy among older patients with chronic diseases by gender. Results: The factors influencing health literacy differed by gender. Male health literacy was related to education background, number of children, monthly income, duration of chronic disease and chronic disease self-efficacy. For females, health literacy was associated with age, education background, monthly income, duration of chronic disease and chronic disease treatment. Conclusions: Healthcare providers should focus on the above-mentioned factors that could help identify those with low health literacy differ base on gender. Gender-specific strategies should be developed to improve the health literacy of older patients with chronic diseases and strengthen their chronic disease management.